Covid adalah pageblug: Makna dan respon masyarakat terhadap pandemi di Desa Pancasila, Sukoreno Jember - Fitriatul Hasanah; Nur Hadi; Ahmad Arif Widianto (Universitas Negeri Malang, 2021)
The last decade of 2019, the world was in an uproar with the emergence of the corona virus disease (Covid-19) outbreak which first appeared in the city of Wuhan, China and spread throughout all countries including Indonesia. Covid-19 has had a significant impact in terms of socio-cultural and economic aspects. This study aims to describe the impact of Covid-19 which has contributed to the social transformation of the people of Pancasila Village, Sukoreno in maintaining the stability of government regulations against Covid-19. This research uses qualitative methods by collecting data through interviews and observations. Interviews were conducted with the village government, religious leaders, and the people of Pancasila Village, Sukoreno. The data analysis technique used an interactive model. The results showed that the 'pagebluk' paradigm is still strongly attached to rural communities in responding to the Covid-19 virus. Pagebluk is an assumption that is believed by the community in the form of